Fractures of the distal clavicle: comparison between two surgical treatment methods - José Carlos Souza Vilela; Ronaldo Percopi de Andrade; Lucas Braga Jacques Gonçalves; Thalles Leandro Abreu Machado; Mario Roberto Chaves Correa Filho; Ivana Duval-Araújo (2015)
To compare the clinical and radiographic results from osteosynthesis of fractures of the lateral third of the clavicle, using two methods: T plates or anchors together with Kirschner wires.Fifteen patients of mean age 34.3 years (range: 19-57) and mean follow-up 22.7 months (range: 14-32) were evaluated. In nine cases, a T plate was used; and in six cases, coracoclavicular fixation was used with anchors in the coracoid process and Kirschner wires through the acromioclavicular joint. The evaluation included the Constant score, personal satisfaction and radiographic assessment.Both types of treatment achieved consolidation in all cases. Group 1 presented a higher Constant score (83.4) than that of Group 2 (76.4) (p = 0.029). Neither of the techniques presented any severe complications, and mild complications were only observed in Group 2 (80%), mostly consisting of migration of the Kirschner wire and superficial infection.Surgical treatment of fractures of the distal clavicle using T plates provided the same consolidation rate as shown by coracoclavicular fixation with anchors in the coracoid process and Kirschner wires through the acromioclavicular joint, and better clinical results.Level III evidence was obtained. Comparative retrospective study and therapeutic study were performed.Comparar os resultados clínicos e radiográficos da osteossíntese de fraturas do terço lateral da clavícula com dois métodos: placa T ou âncoras associadas aos fios de Kirschner.Foram avaliados 15 pacientes com média de idade de 34,3 anos (19–57) e seguimento médio de 22,7 meses (14–32). Em nove casos foi usada a placa T e em seis casos a fixação coracoclavicular com âncoras no processo coracoide e fios de Kirschner através da articulação acromioclavicular (AC). A avaliação incluiu o escore de Constant, satisfação pessoal e avaliação radiográfica.Ambas as modalidades de tratamento obtiveram consolidação em todos os casos. O Grupo 1 apresentou escore de Constant mais elevado (83,4) quando comparado com o Grupo 2 (76,4) p = 0,029. Nenhuma das técnicas apresentou complicações graves, embora complicações leves tenham sido observadas apenas no Grupo 2 (80%), a maioria delas a migração do fio de Kirschner e infecção superficial.O tratamento cirúrgico das fraturas da clavícula distal com placa T proporciona a mesma taxa de consolidação da fixação coracoclavicular com âncoras no coracoide e fios de Kirschner através da articulação AC e melhores resultados clínicos.Nível III, estudo retrospectivo comparativo, estudo terapêutico.